2021
DOI: 10.1017/dmp.2021.172
|View full text |Cite
|
Sign up to set email alerts
|

Food Insecurity and Affecting Factors in Households With Children During the COVID-19 Pandemic: A Cross-Sectional Study

Abstract: Objective: To examine the incidence of food insecurity and affecting factors in households with children in Turkey during the COVID-19 pandemic. Design: This is a cross-sectional study. Setting: The participants were recruited by the snowball sampling method and the data were collected via a link sent to their smart mobile phones through their social media accounts. Participants: This study included 211 households with at least one child. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…Beyond data on the rate of food insecurity in different groups, several studies have examined risk factors and correlations for food insecurity (for example, [63,65,94,96,97,100,101,[114][115][116]), revealing its association with structural conditions such as poverty, unemployment or low work intensity or employment precarity, housing tenure, low incomes, and low levels of education. The increase in food insecurity risk in households headed by women and those with children is well-documented [117][118][119][120], and new research is emerging on its prevalence among youth [96,116] and older adults [97,121].…”
Section: Correlatesmentioning
confidence: 99%
“…Beyond data on the rate of food insecurity in different groups, several studies have examined risk factors and correlations for food insecurity (for example, [63,65,94,96,97,100,101,[114][115][116]), revealing its association with structural conditions such as poverty, unemployment or low work intensity or employment precarity, housing tenure, low incomes, and low levels of education. The increase in food insecurity risk in households headed by women and those with children is well-documented [117][118][119][120], and new research is emerging on its prevalence among youth [96,116] and older adults [97,121].…”
Section: Correlatesmentioning
confidence: 99%
“…The latest estimated national food insecurity was reported to be 16 % in 2017 according to the Türkiye Nutrition and Health Survey (TNHS) (7) . However, vulnerable groups such as immigrants or low-income populations were documented to have a food insecurity prevalence of up to 60 % (7,8) . In the FAO of the United Nations’ The State of Food Security and Nutrition in the World (SOFI) report, Türkiye with its Syrian refugees was listed among the twenty-two countries in a food crisis situation where conflict is the main driver of acute food insecurity (9) .…”
mentioning
confidence: 99%
“…In Turkey, eighty-six percent of families had monthly incomes below the poverty level which revealed that the pandemic resulted in the loss of at least one employment in one out of every six families, and that more than half of households saw a decrease in monthly income. The studies also suggested that food insecurity increased 2.5 times when the occupation of the household employees was worker or self-employed (Bulucu Büyüksoy et al, 2021). It surged 3.1 times in response to a fall in the household's monthly income.…”
Section: Occupation and Incomementioning
confidence: 96%
“…The type of occupation also plays a critical role in influencing food insecurity. In Turkey, the prevalence is 2.5 times higher among labour-workers and self-employed, which might be explained by the lack of employee wages insurance and workers protection law from the government (Bulucu Büyüksoy et al, 2021;Giacoman et al, 2021). In addition, findings from two developed nations the UK.…”
Section: Background and Rationalmentioning
confidence: 99%
See 1 more Smart Citation